Levantamento dos impactos inerentes à inadequação do saneamento básico - Melo, Juli Emille Pereira de (Universidade Federal Rural do Semi-Árido, 2020)
Basic sanitation is one of the services that provokes the most concern at a global, national and local level, due to the countless impacts that its inadequacy can cause to the health of the population, economy and the environment. This work aims to study the relationship between the inadequacy of basic sanitation and the impacts in the various areas that are affected by this system. For this, a bibliographic research was carried out on specific topics such as: the importance of the functions and services offered by basic sanitation; the situation of sanitation in Brazil; the social, environmental and economic impacts generated by the inadequacy of sanitation services; and, mitigation measures related to impacts. The data shows that sanitation has its importance in preventing disease, additionally its absence or inadequacy can generate health impacts (such as gastroenteritis, bacterial resistance and heart disease); impacts on education, women's safety, work and family income; and also impacts on a nation's economy, such as losses on tourism and investment in health. The necessary measures to be applied that mitigate the problems involving inadequate sanitation were observed.
Keywords: Meio ambiente; impactos; esgotamento sanitário; resíduos sólidos; saúde; CIENCIAS AGRARIAS::ENGENHARIA AGRICOLA